CASCADE REFRIGERATION SYSTEM FOR LOW TEMPERATURES USING NATURAL FLUIDS - Rangel, V. B.; Almeida, A. G. S. (Revista de Engenharia Térmica, 2021)
Cascade refrigeration systems work with two or more serial disposed cycles and can obtain internal temperatures below -60°C, which is necessary for several activities in medicine and scientific research. This paper presents a thermodynamic analysis of cascade system refrigeration using natural refrigerant fluids for ultra-low temperatures. These fluids are environmentally friendly refrigerant and are an alternative to hydro chlorofluorocarbons (HCFCs) and to hydrofluorocarbons (HFCs). Energy and exergy analyses were performed using a thermodynamic model based on the law of conservation of mass and also on the first and second laws of thermodynamics. A simulator was developed to assess the technical practicability of this system, considering it running as a real refrigeration cycle. Natural fluids have best performance energetically and environmentally.